ANALYZING CUSTOMER PREFERENCE TOWARDS PAYMENT SYSTEM: CASH, DEBIT CARD AND CREDIT CARD - Pomantow, Marselina Prisilia Stacy (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Payment system is a tool of payment that purposes to help activity of buyer and seller transaction easier. In this modern area it is required to the instrument payment which easier to bring and practical for usage. Payment system covers the legal and regulatory framework, institutions and mechanisms used to transfer funds in order to settle liabilities arising from economic activities. This research is purposed to analyze the usage of three payment system: cash, drbit card and credit card. This research used the Analythical Hierarchy Process (AHP) as the analyzed data of this research. Population in this research is mainly 200 civil servants in Manado who have been using there payment system. The sample of this research is 30 respondents of  purposive random sampling.Results shows that the most of payment system used based on criteria and subcriteria is credit card. Subcriteria based on are considered by respondents to choose. Promotion, experience, privacy and reducing time considered as factors in the priority security criteria that are highly important in choosing and using the payment systems. Keywords: payments system, debit card, credit card, purchase decision.